(untitled) (Journal of Geography and Environmental Management, 2025)
Currently, soil degradation caused by erosion (runoff) is a pressing issue that requires accurate assessment of its scale and the development of effective preventive measures. Soil erosion is a complex natural-anthropogenic process that leads to the loss of land fertility and causes significant damage to agriculture and the economy. According to its origin, soil erosion is divided into two main types: wind erosion (deflation) and water erosion (runoff). High intensity and heavy precipitation are key factors that accelerate water erosion. The goal of this study is to determine the spatial distribution of the rainfall intensity coefficient (R-factor) and evaluate its role in the quantitative assessment of soil runoff in the Terisakkan River Basin. To achieve this, GIS technologies were used: interpolation of meteorological precipitation data allowed the calculation of R-factor values across the basin area. The Terisakkan River Basin extends approximately 130 km from east to west and 239 km from south to north. The southern part is located in a low mountainous zone, while the northern part lies in a flat area. As a result, precipitation decreases from south to north. Maximum rainfall values (302–325 mm/year) were recorded in the northeastern part, while the minimum values (137–176 mm/year) were observed in the south. The calculated R-factor distribution reflects this pattern: maximum values (151–162) are found in the northeast, and minimum values (68–88) in the south of the basin. This confirms the crucial role of the R-factor in the development of water erosion processes, especially in areas with fine-grained soils and strong winds. The scientific significance of the study lies in clarifying spatial patterns of soil erosion based on R-factor calculations for this territory, and its practical value is in identifying high-risk zones and planning effective anti-erosion measures